Cell transformation and tumor induction by Abelson murine leukemia virus in the absence of helper virus. - Green, P L (1987)
We investigated the role of the Moloney helper virus, Moloney murine leukemia virus (Mo-MuLV), in cell transformation and tumor induction by the defective Abelson murine leukemia virus (Ab-MuLV). A molecular clone of Ab-MuLV (P160 strain) was transfected into the psi 2 packaging cell line, and helper virus-free Ab-MuLV (psi 2) was harvested from the supernatant medium. Ab-MuLV (psi 2) was as efficient as helper virus-containing Ab-MuLV (Mo-MuLV) in the transformation of primary bone marrow cells in vitro. Inoculation of weanling BALB/c mice with Ab-MuLV (psi 2) induced nonthymic pre-B-cell lymphomas with high efficiency and short latency (28 days). Adult BALB/c mice were less sensitive to tumor induction by a factor of 100. Ab-MuLV (psi 2) did not induce tumors in weanling C57BL/6 mice, unlike Ab-MuLV (Mo-MuLV). Examination of the proviral integration pattern in Ab-MuLV (psi 2)-induced tumor cell DNA revealed that each of the tumors contained a single integrated provirus. Immunoprecipitation of viral-encoded proteins in helper virus-free tumor cell lines detected the P160 Ab-MuLV-transforming protein; however, no trace of the gag, pol, and env helper virus-encoded proteins was found. Our results indicate that integration and expression of a single Ab-MuLV genome is sufficient for efficient transformation of primary bone marrow cells by Ab-MuLV in vitro and tumor induction in susceptible mice. However, the helper virus may contribute to tumor induction in weanling resistant mice.